Factors affecting employee morale in selected BPO Customer Service Agents in post-pandemic shift in NCR - Alonzo, Aaron Christian Y, Amores, Clarisse B., de Guzman, Jim Cymer O., Empeno, Romelyn A., Hife, Jehan N., Macapagal, Macriz C., Ocana, Jeshrick Renz F., Orpilla, Carleene Sophia A., Ramos, John Larry F., Reyes, Randolfh Alleen V. 4 0 16; 5 (2022)
u
Research Paper: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2022.
Keywords: 2 -- 0; 6; 20; 20; 2